The Female FTSE Board Report 2013: False Dawn of Progress for Women on Boards? - Sealy, Ruth; Vinnicombe, Susan (Cranfield University School of Management, 2013)
The last year has seen extraordinary changes for women on boards. The number of women holding FTSE 100 board seats is 169 (holding 194 seats), an increase of 28 on the 2012 figures. The overall percentage of female-held board directorships is 17.3%, an uplift of 2.3% on last year’s figure. The number of FTSE 100 companies with all-male boards has dropped to seven and two thirds (67%) of the FTSE 100 have more than one woman on their board. In the first six months the pace of change was extremely encouraging. There was a sharp increase in the percentage of new appointments going to women on both FTSE 100 and 250 boards, peaking at 44% and 36% respectively. However, those high levels were short-lived and over the past six months they have dropped to 26% and 29% respectively, showing a considerable gap from the 33% required to reach Lord Davies’ target of 25% women on boards by 2015. That target for the FTSE 100 companies is still in sight but only if the rate of new appointments going to women regains momentum promptly and there is concern that complacency may be setting in, which the UK economy cannot afford.